Elaboration of a consensual definition of de-escalation allowing a ranking of β-lactams. (July 2015) - Weiss, E.; Zahar, J.-R.; Lesprit, P.; Ruppe, E.; Leone, M.; Chastre, J.; Lucet, J.-C.; Paugam-Burtz, C.; Brun-Buisson, C.; Timsit, J.-F.; ,
Abstract: Empirical broad spectrum antimicrobial therapy prescribed in life-threatening situations should be de-escalated to mitigate the risk of resistance emergence. Definitions of de-escalation (DE) vary among studies, thereby biasing their results. The aim of this study was to provide a consensus definition of DE and to establish a ranking of β-lactam according to both their spectra and their ecological consequences. Twenty-eight experts from intensive care, infectious disease and clinical microbiology were consulted using the Delphi method (four successive questionnaires) from July to November 2013. More than 70% of similar answers to a question were necessary to reach a consensus. According to our consensus definition, DE purpose was to reduce both the spectrum of antimicrobial therapy and the selective pressure on microbiota. DE included switching from combination to monotherapy. A six-rank consensual classification of β-lactams allowing gradation of DE was established. The group was unable to differentiate ecological consequences of molecules included in group 4, i.e. piperacillin/tazobactam, ticarcillin/clavulanic acid, fourth-generation cephalosporin and antipseudomonal third-generation cephalosporin. Furthermore, no consensus was reached on the delay within which DE should be performed and on whether or not the shortening of antibiotic therapy duration should be included in DE definition. This study provides a consensual ranking of β-lactams according to their global ecological consequences that may be helpful in future studies on DE. However, this work also underlines the difficulties of reaching a consensus on the relative ecological impact of each individual drug and on the timing of DE.